VIVÊNCIA DO PROJETO VER-SUS NO MUNICÍPIO DE SOBRAL-CE: RELATO DE EXPERIÊNCIA - Sales da Silva Filho, Gonzaga; Moita Morais, Andreza; Farias Gomes, Diógenes; de Oliveira Alves, Juliana; Maria Gomes Maciel, Rosa; Vieira dos Santos, Ana Aline; Ximenes Dias, Isa Carolina (SANARE - Revista de Políticas Públicas, 2015)
-